2020
DOI: 10.1097/gox.0000000000002882
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Saline versus Silicone Gel Implants for Subpectoral Breast Augmentation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Through outcome surveys and ultrasound evaluation, Swanson objectively found that the visible and palpable rippling rates of silicone gel and saline implants were similar [24]. In his study, the saline implants were filled to the manufacturer's recommended fill volume.…”
Section: Implant Look and Feelmentioning
confidence: 99%
“…Through outcome surveys and ultrasound evaluation, Swanson objectively found that the visible and palpable rippling rates of silicone gel and saline implants were similar [24]. In his study, the saline implants were filled to the manufacturer's recommended fill volume.…”
Section: Implant Look and Feelmentioning
confidence: 99%
“…Cosmetically, the appeal of either is arguable, with different studies producing results that suggest that both implant types provide a similar degree of ripple and animation deformity, an undesirable effect of the implant [5].…”
Section: Discussionmentioning
confidence: 99%